The role of free radical stress in the etiology of Pendred syndrome in a mouse model - Singh, Ruchira (Kansas State University, 2008)
Pendred syndrome is characterized by sensorineural deafness and post-pubertal goiter. It is caused by mutations in the anion exchanger, pendrin (SLC26A4). The purpose of this study was to understand the etiology of Pendred syndrome using a mouse model. Different methods of amplification from nanogram amounts of starting RNA were evaluated for gene array application. Gene arrays were performed and free radical stress markers were compared between the stria vascularis and the thyroid of the Slc26a4+/- and Slc26a4-/- mice. Hearing loss in Slc26a4-/- mice is linked to the loss of Kcnj10 protein expression and consequently the loss of endocochlear potential. To understand the mechanism of hearing loss in Slc26a4-/- mice, progressive loss of Kcnj10 protein expression in stria vascularis of Slc26a4-/- mice was assessed, the modulation of Kcnj10 protein expression by free radical stress in cultured stria vascularis and in an heterologous expression system was evaluated. To characterize the thyroid pathology, pendrin expression in the thyroid of Slc26a4+/- mice was measured in a developmental study and correlated with serum thyroxine (T4) levels of Slc26a4+/- and Slc26a4-/- mice over a developmental time course. All tested methods of RNA amplification were suitable for gene array application and demonstrated high internal consistency. Intermethod comparisons revealed variations in data, suggesting that a single amplification method ought to be used within a given experiment. Markers of free radical stress were increased in the stria vascularis of Slc26a4-/- mice before the onset of hearing. Progressive loss of Kcnj10 expression was seen in Slc26a4-/- mice at the onset of hearing. Furthermore, free radical stress modulated the expression of Kcnj10 in cultured stria vascularis and in a heterologous expression system. The pendrin mRNA expression was marginal in the thyroid and did not correlate with serum T4 levels. Further, absence of pendrin did not affect free radical stress markers in the thyroid. These data suggest that free radical stress-mediated loss of Kcnj10 expression in stria vascularis contributes to deafness in the Pendred syndrome mouse model and that pendrin is not essential for the function of mouse thyroid gland.
Keywords: Free radical stress; Pendred syndrome; Biology, Animal Physiology (0433); Biology, Molecular (0307); Biology, Veterinary Science (0778)